High-Level Production of Recombinant Snowdrop Lectin in Sugarcane and Energy Cane - Padilla, Carmen S.; Damaj, Mona B.; Yang, Zhong-Nan; Molina, Joe; Berquist, Brian R.; White, Earl L.; Solís-Gracia, Nora; Da Silva, Jorge; Mandadi, Kranthi K. (Frontiers in Bioengineering and Biotechnology, 2020)
Sugarcane and energy cane (Saccharum spp. hybrids) are ideal for plant-based production of recombinant proteins because their high resource-use efficiency, rapid growth and efficient photosynthesis enable extensive biomass production and protein accumulation at a cost-effective scale. Here, we aimed to develop these species as efficient platforms to produce recombinant Galanthus nivalis L. (snowdrop) agglutinin (GNA), a monocot-bulb mannose-specific lectin with potent antiviral, antifungal and antitumor activities. Initially, GNA levels of 0.04% and 0.3% total soluble protein (TSP) (0.3 and 3.8 mg kg-1 tissue) were recovered from the culms and leaves, respectively, of sugarcane lines expressing recombinant GNA under the control of the constitutive maize ubiquitin 1 (Ubi) promoter. Co-expression of recombinant GNA from stacked multiple promoters (pUbi and culm-regulated promoters from sugarcane dirigent5-1 and Sugarcane bacilliform virus) on separate expression vectors increased GNA yields up to 42.3-fold (1.8% TSP or 12.7 mg kg-1 tissue) and 7.7-fold (2.3% TSP or 29.3 mg kg-1 tissue) in sugarcane and energy cane lines, respectively. Moreover, inducing promoter activity in the leaves of GNA transgenic lines with stress-regulated hormones increased GNA accumulation to 2.7% TSP (37.2 mg kg-1 tissue). Purification by mannose-agarose affinity chromatography yielded a functional sugarcane recombinant GNA with binding substrate specificity similar to that of native snowdrop-bulb GNA, as shown by enzyme-linked lectin and mannose-binding inhibition assays. The size and molecular weight of recombinant GNA were identical to those of native GNA, as determined by size-exclusion chromatography and MALDI-TOF mass spectrometry. This work demonstrates the feasibility of producing recombinant GNA at high levels in Saccharum species, with the long-term goal of using it as a broad-spectrum antiviral carrier molecule for hemopurifiers and in related therapeutic applications.